1991
DOI: 10.1002/aja.1001900307
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative changes in steroidogenic organelles in the corpus luteum of the pregnant rat in relation to progestin secretion on day 16 and in the morning and afternoon of day 22

Abstract: The present study was carried out to determine whether the major steroidogenic organelles of luteal cells quantitatively reflect variations in ovarian steroid secretion rates during pregnancy in the rat. Assessments were made on day 16 and in the morning (AM) and afternoon (PM) of day 22 (term is day 23). Ovarian steroidogenesis differs both quantitatively and qualitatively between these stages of pregnancy, so together they provide an ideal physiological model to study structural-functional relationships in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…It is known that when granulosa cells differentiate into corpus luteum, there is accompanying hypertrophy of the agranular endoplasmic reticulum, which seems to be further enhanced during pregnancy. This hypertrophy of the endoplasmic reticulum appears to reflect an increased demand for steroidogenesis and is also responsible for increased total protein observed in the pregnant corpus luteum [ 43 , 44 ]. Our finding that GPx8 is also present in granulosa lutein cells probably suggests that increased steroidogenesis in the corpus luteum needs protection against OS development.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that when granulosa cells differentiate into corpus luteum, there is accompanying hypertrophy of the agranular endoplasmic reticulum, which seems to be further enhanced during pregnancy. This hypertrophy of the endoplasmic reticulum appears to reflect an increased demand for steroidogenesis and is also responsible for increased total protein observed in the pregnant corpus luteum [ 43 , 44 ]. Our finding that GPx8 is also present in granulosa lutein cells probably suggests that increased steroidogenesis in the corpus luteum needs protection against OS development.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that total progestin (progesterone plus 20a-hydroxypregn-4-en-3-one) secretion rates in the rat fall from 32 pglhr per ovary on day 16 to 10 pglhr per ovary on the morning (1100 hr) of day 22 (day 22 AM) and rise again to 23 pglhr per ovary in the afternoon (1500 hr) of the same day (day 22 PM). These changes are not accompanied by any comparable changes in CL volume (Waddell et al, 1989) or in the amount and surface areas of steroidogenic organelles (Dharmarajan et al, 1991). The present work therefore was carried out to test whether changes in transport structures would more closely reflect progestin secretion rates and the increase in total ovarian and CL blood flow observed over days 16 to 22 (Bruce et al, 1984).…”
Section: Introductionmentioning
confidence: 94%
“…These changes are not accompanied by any comparable changes in CL volume (Waddell et al, 1989) or in the amount and surface areas of steroidogenic organelles (Dharmarajan et al, 1991). The present work therefore was carried out to test whether changes in transport structures would more closely reflect progestin secretion rates and the increase in total ovarian and CL blood flow observed over days 16 to 22 (Bruce et al, 1984).…”
Section: Introductionmentioning
confidence: 94%
“…The corpus luteum (CL) is a fully differentiated structural and functional unit that undergoes apoptosis following the cyclic withdrawal of tropic support [6]. CL apoptosis is best characterized by the loss of steroidogenic potential [7,8] and luteal cell death [9][10][11].…”
Section: Introductionmentioning
confidence: 99%